Scientific degree in Russia: reality and prospects - Vladimir V. Laptev; Svetlana A. Pisareva; Alla P. Tryapitsyna (Высшее образование в России)
The article examines the history of formation of scientific degrees in Russia, analyzes the causes of the devaluation of degrees in modern Russia, reveals the directions of optimization of training of researchers in postgraduate course, describes possible models of the integration of the domestic postgraduate courses into the open European scientific and educational environment.